1997
DOI: 10.1007/bf02910672
|View full text |Cite
|
Sign up to set email alerts
|

Serum and hair zinc levels in epileptic children taking valproic acid

Abstract: This study was performed to investigate the serum and hair zinc levels in patients epilepsy diagnoses who were intended to be put on valproic acid (VA) monotherapy and had never ingested antiepileptics before. A total of 16 patients having normal growth, development and nutrition was selected as Group 1, and Group 2 was made up of 10 patients who had received VA monotherapy for 2 yrs or more and had normal growth, development, and nutrition characteristics. A control group (Group 3) was formed of 15 subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Steidl et al (72) Hair analysis has been used to evaluate the trace element status in the body (74 -76). Hair levels of Zn 2+ were found to be decreased in patients on AEDs compared to those in controls (77,78,30). In the prospective study done by Altunbasak et al (78), the serum and hair levels of Zn 2+ were found to be higher in untreated epileptic patients than those treated with VPA and controls and returned to normal level after VPA treatment.…”
Section: Zincmentioning
confidence: 99%
“…Steidl et al (72) Hair analysis has been used to evaluate the trace element status in the body (74 -76). Hair levels of Zn 2+ were found to be decreased in patients on AEDs compared to those in controls (77,78,30). In the prospective study done by Altunbasak et al (78), the serum and hair levels of Zn 2+ were found to be higher in untreated epileptic patients than those treated with VPA and controls and returned to normal level after VPA treatment.…”
Section: Zincmentioning
confidence: 99%
“…The various drugs causing nail changes are chemotherapeutic agents, psoralens, phenothiazines, lithium, The exact etiopathogenesis of AED-induced onychomadesis is not known. [17] The association of AED-induced isolated onychomadesis is highlighted in our case. Exposure to anticonvulsants such as diphenylhydantoin, trimethadone, valproic acid, and carbamazepine during pregnancy is associated with fingernail and toe-nail hypoplasia in the newborn.…”
mentioning
confidence: 63%
“…On the other hand, the number of studies focusing on the trace element levels of epileptics prior to and during treatment is rather limited (14)(15)(16)(17) It is important to underline that all patients treated in our study were precribed drugs at the normal dosage and all serum levels of AEDs were within the therapeutic range. Age may have been one of the factors why serum Zn levels were significantly lower in PB group.…”
Section: Discussionmentioning
confidence: 92%